Digital Technology used By English Students In Learning English Skills - friska dwinda fitri03; Ria Angraini; Epi Wadison (Teaching English and Language Learning English Journal, 2025)
Digital technology that is used to improve students' English learning skills currently has the aim of developing an English application, such as YouTube, learning application, social media, web, and etc. The students can access from handphone or laptop/computer everywhere, so that they can easier to learning English. It is also can improve the students motivation to learn, because with digital technology the students feel enjoy and not bored to improve their English skills. The objective of this research was to find out digital learning technolgy used by English students in learning English skills. The method used in this research was descriptive qualitative method. The instrument of this research was questionnaire about digital technology in learning English skills. It found that in Speaking skill the students used digital technologies: Social Media (Instagram, Tiktok and Facebook),Youtube, movie,music and Google Translate. In Listening the students used digital technologies: Youtube, Music, Movie. In Reading Skill the students used digital technologies: Social Media (Instagram, TikTOk Facebook), Video and Google Translate. In Writing skill the students used digital technologies: Google translate and Social Media. The dominant digital technology useb by students is Social Media. It is suggested for Englsih students to use more digital technology to improve their English Skills. Key words: Digital Technology, Four Skills, Digital Technology in English Skills